Application of Trio-Whole Exome Sequencing in Genetic Diagnosis and Therapy in Chinese Children With Epilepsy - Jiang, Tiejia; Gao, Jia; Jiang, Lihua; Xu, Lu; Zhao, Congying; Su, Xiaojun; Shen, Yaping; Gu, Weiyue; Kong, Xiaohong; Yang, Ying; Gao, Feng (Frontiers in Molecular Neuroscience, 2021)
Epilepsy is one of the most common neurological disorders in pediatric patients with other underlying neurological defects. Identifying the underlying etiology is crucial for better management of the disorder. We performed trio-whole exome sequencing in 221 pediatric patients with epilepsy. Probands were divided into seizures with developmental delay/intellectual disability (DD/ID) and seizures without DD/ID groups. Pathogenic (P) or likely pathogenic (LP) variants were identified in 71/110 (64.5%) patients in the seizures with DD/ID group and 21/111 (18.9%) patients in the seizures without DD/ID group (P < 0.001). Eighty-seven distinct P/LP SNVs (single nucleotide variants) /Indels (insertion deletions) were detected, with 55.2% (48/87) of them being novel. All aneuploid and P/LP CNVs (copy number variants) larger than 100 Kb were identifiable by both whole-exome sequencing and CNVseq in one hundred and twenty-three of individuals (41 pedigrees). Ten of P/LP CNVs in nine patients and one aneuploidy variant in one patient (Patient #56, #47, XXY) were identified by CNVseq. Herein, we identified seven genes (NCL, SEPHS2, PA2G4, SLC35G2, MYO1C, GPR158, and POU3F1) with de novo variants but unknown pathogenicity that were not previously associated with epilepsy. Potential effective treatment options were available for 32 patients with a P/LP variant, based on the molecular diagnosis. Genetic testing may help identify the molecular etiology of early-onset epilepsy and DD/ID and further aid to choose the appropriate treatment strategy for patients.